2022
DOI: 10.7759/cureus.31857
|View full text |Cite
|
Sign up to set email alerts
|

Public Knowledge, Attitudes, and Practices Towards Antibiotic Use and Antimicrobial Resistance in the Western Region of Saudi Arabia

Abstract: IntroductionAntimicrobial resistance (AMR) is one of the major concerns for global health. Inappropriate use of antibiotics is speeding up the process of AMR. The aim of this study was to assess the knowledge, attitude, and practices (KAP) of the population of the western region of Saudi Arabia towards antibiotic use and AMR. MethodsA cross-sectional study was conducted using an online questionnaire via social media platforms. It consisted of four parts: first, the participant's sociodemographic characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
0
11
2
Order By: Relevance
“…This is a positive practice that aligns with wise antibiotic use. This finding is inconsistent with the results of previous studies conducted in Lithuania [ 21 ], Malaysia [ 18 ], and Saudi Arabia [ 22 ], where only 28.5%, 17%, and 25% of participants, respectively, reported storing antibiotics at home for future use. Moreover, according to research done by AlRukban et al in 2020, it was found that almost two-thirds of the participants had antibiotics stored inside their households [ 23 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is a positive practice that aligns with wise antibiotic use. This finding is inconsistent with the results of previous studies conducted in Lithuania [ 21 ], Malaysia [ 18 ], and Saudi Arabia [ 22 ], where only 28.5%, 17%, and 25% of participants, respectively, reported storing antibiotics at home for future use. Moreover, according to research done by AlRukban et al in 2020, it was found that almost two-thirds of the participants had antibiotics stored inside their households [ 23 ].…”
Section: Discussioncontrasting
confidence: 99%
“…According to the survey conducted in Kuwait, around 64.7% of the participants expressed confidence in physicians to obtain antibiotics on a valid prescription [ 17 ]. A Saudi Arabian study reported that a significant proportion of respondents (72.6%) expressed agreement with the notion that antibiotics should not be obtained without a prescription [ 22 ]. According to the research conducted in Indonesia, around 40% of the participants reported purchasing antibiotics from pharmacies but without obtaining prescriptions [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMR [17]; the Western region of Saudi Arabia (55%) [45,46]; the general rural population in low-income and middle-income in South-East Asia: Chiang Rai, Thailand (74.8%), and Salvan (62.5%) [47]. Furthermore, in a meta-analysis of 24 studies comprising 40747 general population, Gualano et al, found that approximately 59% of people were aware of AMR [46].…”
Section: Plos Onementioning
confidence: 99%
“…This behavior can contribute to developing bacterial resistance, which can be challenging to treat. In the study conducted in the western region of Saudi Arabia, over 50% of the participants stopped taking antibiotics after they felt improvement [19] . Conversely, in a Romanian study, only 10% of participants discontinued antibiotic use once they felt better, while approximately 60% continued taking them until the doctor-recommended course was completed [26] .…”
Section: Discussionmentioning
confidence: 99%